Coactosin-like protein 1 regulates integrity and repair of model intestinal epithelial barriers via actin binding dependent and independent mechanisms - Lechuga, Susana; Marino-Melendez, Armando; Davis, Austin; Zalavadia, Ajay; Khan, Afshin; Longworth, Michelle S.; Ivanov, Andrei I. (Frontiers in Cell and Developmental Biology, 2024)
The actin cytoskeleton regulates the integrity and repair of epithelial barriers by mediating the assembly of tight junctions (TJs), and adherens junctions (AJs), and driving epithelial wound healing. Actin filaments undergo a constant turnover guided by numerous actin-binding proteins, however, the roles of actin filament dynamics in regulating intestinal epithelial barrier integrity and repair remain poorly understood. Coactosin-like protein 1 (COTL1) is a member of the ADF/cofilin homology domain protein superfamily that binds and stabilizes actin filaments. COTL1 is essential for neuronal and cancer cell migration, however, its functions in epithelia remain unknown. The goal of this study is to investigate the roles of COTL1 in regulating the structure, permeability, and repair of the epithelial barrier in human intestinal epithelial cells (IEC). COTL1 was found to be enriched at apical junctions in polarized IEC monolayers in vitro. The knockdown of COTL1 in IEC significantly increased paracellular permeability, impaired the steady state TJ and AJ integrity, and attenuated junctional reassembly in a calcium-switch model. Consistently, downregulation of COTL1 expression in Drosophila melanogaster increased gut permeability. Loss of COTL1 attenuated collective IEC migration and decreased cell-matrix attachment. The observed junctional abnormalities in COTL1-depleted IEC were accompanied by the impaired assembly of the cortical actomyosin cytoskeleton. Overexpression of either wild-type COTL1 or its actin-binding deficient mutant tightened the paracellular barrier and activated junction-associated myosin II. Furthermore, the actin-uncoupled COTL1 mutant inhibited epithelial migration and matrix attachment. These findings highlight COTL1 as a novel regulator of the intestinal epithelial barrier integrity and repair.